Potencial do cipó - uva (Serjania lethalis) como fonte de néctar para a exploração apícola na Chapada do Araripe - Alves, Társio Thiago Lopes (2013)
The species Serjania lethalis A.St.-Hil. is a native plant found in all regions of Brazil, like North, Northeast, Midwest, Southeast and South. It is associated with many biomes, such as Amazon, Caatinga, Cerrado, Atlantic Forest and Pantanal. In Ceará, this species is found in a Cerrado disjunction in the Araripe plateau, and it is known popularly as croapé, cipó - uva, and cipó – três - quinas. Although it is exploited for honey production for over twenty years in Araripe Plateau, the scientific studies about this species are few in number. Therefore, the present study aimed to investigate the potential of this plant to apicultural exploitation in the region. To this end, we studied the floral biology, botanical aspects, pollination requirements, flower visitors, foraging behavior of the honeybee (Apis mellifera), the carrying capacity of apiaries and also the characteristics of the honey produced. The study was carried out from 2008 to 2012 in Crato, Jardim, Juazeiro do Norte, Santana do Cariri (Ceará) and Moreilândia (Pernambuco). The data were analyzed through analysis of variance and means were compared by Tukey test (5%), using the SAS statistical software version 9.1 and the t test (5%) using the program Microsoft Office Excel 2007. The results showed that the species is a plant andromonoecious and presents a diclinous or unisexual phase (with male flowers) and another hermaphroditic or monoecious phase, besides presenting an annual flowering phase that lasts four months (August to November). The flowers are produced in axillary inflorescences of the type thyrsus, and 5:00 h 73.75% of the buds were open. The nectar secretion pattern varied over the years and its concentration was higher during the afternoon. The inflorescences lasted 35 days, with a range in length from 20.5 to 22.68 cm (Santana do Cariri) and from 13.47 to 21.89 cm (Moreilândia), 86.76 to 154.90 flowers/inflorescence (Santana do Cariri) and 58.64 to 128.92 flowers/inflorescence (Moreilândia), and 17.35 to 21.30 inflorescences/branch (Santana do Cariri) and 12.20 to 16.60 inflorescences/branch (Moreilândia). The cipó - uva fruits are dry and indehiscent of the type samara, with characteristics of an anemochoric seed dispersal syndrome, and the open pollination yielded more fruits set in both counties, differing from other types of pollination. The species depends on their biotic agents in order to accomplish its pollination, because the wind cannot carry the cipó - uva pollen grains, and the flower is unable to promote self-pollination. The family Apidae was the most frequent among the insect visitors, especially the species Apis mellifera and Trigona spinipes. The foraging by Apis mellifera occurs throughout the day, with the highest peak at 9 h, collecting, exclusively, nectar either in male as in hermaphroditic flowers. In general, the Africanized bee colonies distributed in a natural cipó - uva area in the Araripe Plateau (2008) and Santana Cariri (2008 and 2010) showed a larger honey storage area and a smaller brood area regarding to the total comb area, and also a satisfactory pollen flow. The polifloral honey produced fits within the Brazilian legislation for all physicochemical parameters analyzed, and showed no contamination by molds, yeasts and total coliforms. In sensory acceptance, the cipo - uva honey was approved by the panelists for the attributes of color, flavor, aroma, viscosity and overall acceptance, especially the flavor attribute that was the most appreciated by the panelists. It was concluded that the cipó - uva (Serjania lethalis) requires biotic agents to promote its pollination and consequently it is not able to promote self-pollination. The species is is quite attractive to insects, predominantly honey bees, with only nectar as a food reward. Thus, this species is able to keep well-developed colonies in apiaries, and it presents a honey suitable for the human consumption, however there is a need to improve the management of the colonies in the region in order to avoid compromising honey production.